Paper quality of the National Library Board of Singapore's legal deposit collection as an indicator of the collection's longevity - Parminder Kaur. (2011)
The primary aim of this thesis is to derive some indication as to whether the Legal Deposit Collection (which forms part of the national heritage collection) of the National Library Board of Singapore is deteriorating or will deteriorate in the near future. It is necessary to derive such an indication because ignorance regarding the possible deterioration of the Legal Deposit Collection (LDC) could lead to the eventual loss of national heritage material, a loss which is not affordable.